ANALYSIS OF SOCIAL PROBLEM IN A GOOD MAN IS HARD TO FIND BY FLANNERY O’CONNOR - Hani, Mohamad (Universitas Muhammadiyah Palembang, 2019)
This study aims to describe the problems of social problems contained in the short story